Faktor-faktor Budaya Organisasi, Suatu Studi Pada Prodi Administrasi Bisnis (ADBIS) - Telkom University Bandung [Factors Influencing Organizational Culture: A Study of the Business Administration Program (ADBIS) at Telkom University Bandung] - Astadi Pangarso; Renny Rengganis (Universitas Pelita Harapan, 2015)
Organizations exist because of the human need for relationships, interaction, communication, and socializing one to another to meet a common goal. Organizational culture becomes an important part that influences the effectiveness of the organization (the term for the fulfillment of the purpose of the organization). This study aims to determine the organizational culture conditions at Prodi Adbis Tel-U by using indicators from the Denison organizational culture model that show involvement, consistency, adaptability and mission. In addition to a theoretical study of the importance of organizational culture, the background for this study is a new formation at Tel-U in which there are Adbis Prodi, in recognition of the organization's culture conditions. Adbis through this research can contribute to gradually building a strong organizational culture where Adbis is aligned with the culture of Tel-U. The research method is a quantitative method with data collection using questionnaires sampling populations of faculty and staff at Prodi Adbis Tel-U with as many as 41 people processed using descriptive statistics. The results showed the overall average of the culture of the organization in the department of the Tel-U Adbis FKB including very low category with the highest score on the mission and the lowest subvariable on involvement.